2007
DOI: 10.1101/gad.1563007
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite stimulatory action of the Hop2–Mnd1 complex on the Rad51 recombinase

Abstract: The HOP2 and MND1 genes are indispensable for meiotic recombination. The products of these genes associate to form a stable heterodimeric complex that binds DNA and stimulates the recombinase activity of Rad51 and Dmc1. Here we conduct molecular studies to delineate the action mechanism of the Hop2-Mnd1 complex. We present evidence to implicate Hop2 as the major DNA-binding subunit and Mnd1 as the prominent Rad51 interaction entity. Hop2-Mnd1 stabilizes the Rad51-single-stranded DNA (ssDNA) nucleoprotein filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
151
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(165 citation statements)
references
References 53 publications
14
151
0
Order By: Relevance
“…The HOP2-MND1 complex is one such DMC1 partner. Biochemical studies have shown that, like RAD51AP1 (7,8), HOP2-MND1 preferentially binds dsDNA over ssDNA (11,12) and promotes DMC1-mediated D-loop formation via functional synergy with the DMC1 presynaptic filament in duplex capture and synaptic complex assembly (12). We have found no evidence for physical interaction of RAD51AP1 and HOP2-MND1 or functional synergy of these two factors in the enhancement of the DMC1-mediated D-loop reaction.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…The HOP2-MND1 complex is one such DMC1 partner. Biochemical studies have shown that, like RAD51AP1 (7,8), HOP2-MND1 preferentially binds dsDNA over ssDNA (11,12) and promotes DMC1-mediated D-loop formation via functional synergy with the DMC1 presynaptic filament in duplex capture and synaptic complex assembly (12). We have found no evidence for physical interaction of RAD51AP1 and HOP2-MND1 or functional synergy of these two factors in the enhancement of the DMC1-mediated D-loop reaction.…”
Section: Discussionmentioning
confidence: 42%
“…We first tested the effect of RAD51AP1 on duplex-DNA capture, using our previously published procedure (11). For this, the DMC1 presynaptic filament was assembled on ssDNA linked to magnetic beads via a streptavidin-biotin bridge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast Rad54 protein, Srs2 helicase, RECQ1 helicase, human Hop2-Mnd1 complex, and yeast and human RPA were purified to near homogeneity from E. coli cells tailored to express them, as described (Sigurdsson et al 2001;Krejci et al 2003;Cui et al 2004;Van Komen et al 2006;Chi et al 2007). The BLM, RECQ1, and WRN helicase preparations have been used in several of our published studies (e.g., Raynard et al 2006;Hu et al 2007) and they possess a level of DNA-dependent ATPase activity as high as or higher than that reported in the literature (Brosh et al 1999(Brosh et al , 2000Cui et al 2004; data not shown) and, as expected (Brosh et al 1999(Brosh et al , 2000Cui et al 2004), are adept at unwinding a HJ test substrate (Supplemental Fig.…”
Section: Purification Of Other Proteinsmentioning
confidence: 99%